Filosofi Hindu Narasi Banalisme Filosofi Hindu Dalam Konten Wonderland Indonesia 2 Karya Alffy Rev - Kurniasari, Ni Gusti Ayu Ketut; Toni, Ahmad (Fakultas Dharma Duta, 2022)
This study raises the topic of Hindu pghilosophy contained in the Wonderland Indonesia 2 video by Alffy Rev. The method is narrative analysis with secondary text data in the form of videos on the youtube channel. The results show the: the prologue narration describes the historical symbol constructs the were excavated in the garuda mythology, the Majapahit symbol and depict the under or dark culture of the dragon and the light culture of the garuda. The content narration describes the relationship between the historicity of the mythological wolrd of garuda, Majapahit and national values combined with traditionl art of folk songs and supporting costume elements between various dimensions of banality. The element of banality constructed by the text produser describes a narrative about the integration and unification of the dimensions of nature, creation manajement and idependence after destruction in the trisula philosophy wich is integrated in Hindu culture and teachings. In the final naarative, it is described how the relationship between history and the younger generation of Indonesia is as a form of reconstruction of the values struggle and multiculturalism as a reading of the history of mythology, the history of Majapahit, the history of the independence of the Indonesian nation.